Turnover intentions of New Zealand employees : a multi-study comparison of skill levels : Master of Management in Human Resource Management at Massey University, Albany, New Zealand - Eastgate, Lindsay Richard (Massey University, 2015)
This study investigates turnover intentions across three different skill levels of New Zealand employees: low-skilled (Study 1), semi-skilled (Study 2), and skilled (Study 3) using both quantitative and qualitative methods. Specifically, this study first compares job autonomy, supervisor support, and work-life balance towards job satisfaction and turnover intentions and then ultimately, tests a two mediator model in which firstly, work-life balance and then job satisfaction act as the mediators towards turnover intentions. These mediator effects were confirmed by Monte Carlo analysis. Overall, there is strong support across the studies that work-life balance predicts job satisfaction, which in turn predicts turnover intentions. Towards the antecedents, there is uniformity between low-skilled and skilled employee samples, with supervisor support predicting work-life balance and job autonomy predicting both work-life balance and job satisfaction. Finally, this study uses qualitative interviews (Study 4) to add depth to the quantitative results and explore any additional emerging themes, while also providing a personal narrative to the turnover literature, which is often missing. The interviews generally reinforced the quantitative findings although additional themes were found, and two mini-cases were explored regarding actual turnover. Overall, this thesis aids our understanding of turnover intentions across the various skill levels.
Turnover intentions of New Zealand employees : a multi-study comparison of skill levels : Master of Management in Human Resource Management at Massey University, Palmerston North, New Zealand
Keywords: Labour turnover; Job satisfaction; Work-life balance; Employee motivation; Skill levels; New Zealand